Case Report: Novel Arylsulfatase A (ARSA) Gene Mutations in a Patient With Adult-Onset Metachromatic Leukodystrophy Misdiagnosed as Multiple Sclerosis - Xu, Lulu; Zhong, Meixiang; Wang, Yajuan; Wang, Zhihong; Song, Jie; Zhao, Jing; Yu, Hongyun; Yang, Zhencui; Yan, Wenjing; Zheng, Xueping (Frontiers in Neurology, 2021)
Metachromatic leukodystrophy (MLD) is an autosomal recessive hereditary disorder characterized by the accumulation of sulfatide in the central and peripheral nervous systems. Herein, we present the case of an adult patient with MLD who had mild cognitive and psychiatric dysfunctions and severe vision disturbance, who was initially misdiagnosed as multiple sclerosis. Through genetic screening, this patient was later identified to have a full deletion of exon 4 and the novel p.P220L mutation in the arylsulfatase A (ARSA) gene. These mutations are reported for the first time in MLD. These data will help to update the mutation profiles of patients with MLD.